Developing mutually beneficial understandings of academic cultures in an international higher education Master' s degree programme - Niemi, Christine (2018)
International degree programmes (IDPs) in higher education institutions (HEIs) are no new concept. They represent teaching and learning environments (TALEs), in which a variety of academic cultures intersect. The research aims to understand this diverse teaching and learning community. The objective of the study is to particularly explore the student perspectives navigating this TALE. It is hoped that this research will help providers of IDPs better respond to the diverse experiences and backgrounds of their participants.